Interfaith Moderation From The Perspective of Maqasid Syariah: Analysis of Religious Dialogue in The Sorogenen Community Yogyakarta - Muh Rizki; Andre Afrilian; Ardiansyah Ardiansyah; Almi Jera; Sudirwan Sudirwan (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
Religious diversity in Indonesia represents a social reality that can both enrich communal life and generate social tension and conflict. In response to these challenges, the Indonesian government has promoted religious moderation as a strategic framework to foster social harmony, particularly in interfaith relations. This study aims to describe the practice of religious moderation within the Sorogenen community in Yogyakarta and to analyze its relevance to the principles of maqāṣid al-sharī‘ah as a conceptual framework of Islamic law. This research employs an empirical legal method with a conceptual approach. Fieldwork was conducted over a two-week period and involved four key informants, consisting of one religious leader, one neighborhood head, and two community members. Data were collected through in-depth interviews and analyzed using empirical legal analysis alongside an analytical framework of religious dialogue to interpret patterns of interreligious interaction. The findings indicate that the practice of religious moderation in the Sorogenen community is consistent with the fundamental principles of maqāṣid al-sharī‘ah, particularly the protection of religion (ḥifẓ al-dīn). This alignment is reflected in social behaviors that emphasize mutual respect among residents of different religious backgrounds, including interfaith cooperation to ensure security and the smooth conduct of worship activities during religious holidays. Religious dialogue within the community is characterized by an ethical and persuasive approach (mau‘iẓah ḥasanah), positioning religious outreach as a means of fostering peaceful coexistence rather than religious dominance. The originality of this study lies in its integration of maqāṣid al-sharī‘ah with empirically observed practices of religious moderation through interfaith dialogue at the community level. Conceptually, this research contributes to the development of maqāṣid al-sharī‘ah as a normative framework for strengthening religious moderation and social harmony in pluralistic societies.